Atmospheric stability analysis using Convective Available Potential Energy (CAPE) on the rain occurrence in Padang - Yudha Nugraha; Asrul Asrul; Sugeng Nugroho (PILLAR OF PHYSICS, 2017)
Precipitation is ones of many atmospheric phenomena which closed with human activity. There is so many factors in earth atmosphere that can cause precipitation from global into local scale. One of them is atmospheric stability that identified based on convective available potential energy (CAPE). Using of CAPE is to know the characteristics of atmospheric stability and its correlation with precipitation so we can estimate accuracy of CAPE for predicting daily rainfall. Study took location at several areas in Padang as a region which is located in  tropical latitude and divide it based on topographical characteristic such coastal, urban, and slope mountain area. To understand characteristic of atmospheric stability, is used scatterplot between CAPE with precipitation rainfall. Conclusion shows that for all studied area, CAPE value have variation from slight into moderate, with a little case heavy and extreme value. Correlation between CAPE and daily rainfall shows a negative correlation, which has r score less than -0.2. It can be assumed that relationship between CAPE and rainfall is not significantly closed. Hence, we can assume that atmospheric stability has a less relationship for making high intensity precipitation.